2015
DOI: 10.1016/j.biortech.2015.02.113
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide fermentation to ethanol by Clostridium autoethanogenum in a bioreactor with no accumulation of acetic acid

Abstract: Fermentation of CO or syngas offers an attractive route to produce bioethanol. However, during the bioconversion, one of the challenges to overcome is to reduce the production of acetic acid in order to minimize recovery costs. Different experiments were done with Clostridium autoethanogenum. With the addition of 0.75 μM tungsten, ethanol production from carbon monoxide increased by about 128% compared to the control, without such addition, in batch mode. In bioreactors with continuous carbon monoxide supply, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 28 publications
2
61
1
2
Order By: Relevance
“…A counterargument is that ethanol formation from CO-rich BOF gas appears to be favored when the pH in the growth medium is pH 6 rather than pH 5.5 (87,88), i.e., conditions under which ethanol formation via acetic acid reduction to acetaldehyde is less favored (see above). However, these findings were not backed by a more recent study that showed that during growth of C. autoethanogenum on CO at pH 4.7, mainly ethanol was formed, whereas at pH 6 ethanol and acetate were generated in almost equal amounts (89).…”
Section: H 2 Activationmentioning
confidence: 63%
“…A counterargument is that ethanol formation from CO-rich BOF gas appears to be favored when the pH in the growth medium is pH 6 rather than pH 5.5 (87,88), i.e., conditions under which ethanol formation via acetic acid reduction to acetaldehyde is less favored (see above). However, these findings were not backed by a more recent study that showed that during growth of C. autoethanogenum on CO at pH 4.7, mainly ethanol was formed, whereas at pH 6 ethanol and acetate were generated in almost equal amounts (89).…”
Section: H 2 Activationmentioning
confidence: 63%
“…Abubackar and co-workers found that the presence of tungsten significantly improved alcohol production and increased the ethanol/acetate ratio in C. autoethanogenum grown on CO, while the presence of selenium did either not improve ethanol production or even reduce it under the experimental conditions used in their study. 84,85 Metalloenzymes and the presence of trace metals play thus a key role in ethanol production and are expected to have a similar influence in the bioconversion of gaseous C1 substrates to higher alcohols such as butanol and hexanol.…”
Section: Effect Of Medium Compositionmentioning
confidence: 99%
“…Furthermore, some studies also confirm that C. autoethanogenum is a low productivity bacteria in ethanol production compared to other carboxidotrophic strains of Clostridium sp. despite its genetic modified strain has been developed for ethanol commercial scale production by LanzaTech [1,[12][13][14]. C. ragsdaleii and C. carbodixovorans are the recent isolated strains which their potential are still in the exploration [15,16].…”
Section: Introductionmentioning
confidence: 99%